Knowledge among Puerto Rican Women about Risk of Infertility Associated with Overweight and Obesity - González-Sepúlveda, Lorena; Vera-Arroyo, Verushka; Carro, Maria; Ramos-Tollinchi, Lizzie M.; Romaguera, Josefina; Umpierre, Sharee A. (Puerto Rico Health Sciences Journal, 2020)
Objective: Our study sought to evaluate how aware the women attending gynecology clinics at the University of Puerto Rico Medical Sciences Campus (UPRMSC) were of the association between infertility and excess body weight (i.e., overweight and obesity). Methods: Women 21 years old and older attending gynecology clinics at UPR-MSC were invited to participate in this study (n = 234). A self-administered survey was provided to all the women. Logistic regression models were performed to determine associations. Results: About 56.8% of the women were found to be aware of the effects of obesity on fertility; their main source of medical information was their primary doctor. The odds (adjusted for age and annual income) of being aware of the association between obesity and infertility were about 2.41 (95% CI: 1.07–5.42) times higher in women with a BMI greater than or equal to 25 kg/m2 than they were in those with a BMI of less than 25 kg/m2. An interaction by age group (adjusted for BMI) was found for the association between annual income and knowledge of the obesity infertility association (OR≥40 years old: 3.51, 95% CI: 1.41–8.72; OR<40 years old: 0.57, 95% CI: 0.15–2.13). Conclusion: Our study revealed that there is a lack of knowledge regarding the effects of obesity on fertility and identifies characteristics associated with this knowledge. The contents of health-care-provider counseling and the barriers affecting communication between patients and health care providers could be assessed in further studies.